Learning achievement: outdoor learning and naturalist intelligence - Mohammad Adi Supriadi; I Made Astra; M. Japar; Fitriyani Fitriyani (JRTI (Jurnal Riset Tindakan Indonesia), 2020)
This study aims to determine the effect of outdoor learning models and naturalist intelligence on student learning outcomes in science subjects. The research data were obtained through quantitative data in the form of science test results and a Likert scale from a naturalist intelligence questionnaire. Indoor learning treatment was carried out on 20 grade V elementary school students, for outdoor learning treatment was carried out on 20 students with the same level with different schools. The research method used in this research is experimental design. The data used in the study were the results of observations and students' formative test scores. The results of this study indicate that Science learning achievement of students using the outdoor learning model and students using indoor learning models who have high naturalist intelligence supported by statistical hypothesis testing, the value of Sig. (2-tailed) = 0.001 <α = 0.05, then H0 is rejected, so it can be concluded that, there is a significant difference in science learning achievement between groups of students using outdoor learning models and groups of students using indoor learning models.